2020
DOI: 10.18400/tekderg.408019
|View full text |Cite
|
Sign up to set email alerts
|

Ampirik Potansiyel Evapotranspirasyon Tahmin Yöntemlerinin Değerlendirilmesi: Uygulama Konya Kapalı Havzası

Abstract: Evapotranspirasyon, hidrolojik çevrimde kritik bir rol oynar. Ancak havza ve tarla ölçeğinde miktarının tahmini zordur. Bilim insanları, bu konuyu incelemek amacıyla yaygın erişilebilir ölçülmüş değişkenlere dayanan tahminler sağlayan ampirik denklemler geliştirmişlerdir. Blaney-Criddle, Jensen-Haise, Makkink, Turc, Priestley-Taylor ve Hargreaves-Samani adlı altı ampirik yöntemin performansları, Konya Kapalı Havzası'ndaki beş istasyondan alınan günlük meteorolojik veriler kullanılarak FAO-56 Penman-Monteith yö… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The fact that the FAO-56 PM equation requires a large number of meteorological data (i.e., temperature, humidity, radiation, and wind speed) makes the solution of the equation difficult, and obtaining such data is not always possible. Although Allen et al [1] expressed the solvability of the equation using auxiliary formulae based on temperature data for the PM approach, many alternative empirical methods (i.e., temperaturebased, radiation-based, and a combination of them) have been investigated for use in cases where sufficient data are not available [31][32][33][34][35]. For instance, Tabari et al [34] evaluated the performance of thirty-one alternative empirical methods using meteorological data obtained under humid conditions in Northern Iran and the PM method as a reference.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that the FAO-56 PM equation requires a large number of meteorological data (i.e., temperature, humidity, radiation, and wind speed) makes the solution of the equation difficult, and obtaining such data is not always possible. Although Allen et al [1] expressed the solvability of the equation using auxiliary formulae based on temperature data for the PM approach, many alternative empirical methods (i.e., temperaturebased, radiation-based, and a combination of them) have been investigated for use in cases where sufficient data are not available [31][32][33][34][35]. For instance, Tabari et al [34] evaluated the performance of thirty-one alternative empirical methods using meteorological data obtained under humid conditions in Northern Iran and the PM method as a reference.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the data revealed that, in general, the best results were attained with the Blaney-Criddle and Hargreaves methods compared to the PM equation; mass transfer-based approaches underestimated ET, whereas overestimations were more dominant in temperature-based and radiation-based methods. Sarlak and Bagcaci [35] evaluated the performances of six empirical ET approaches, namely Blaney-Criddle, Jensen-Haise, Makking, Turc, Priestley-Taylor, and Hargreaves-Samani, compared to the PM method using daily meteorological data from five stations in Konya Closed Basin. They concluded that in the absence of daily observation data, the Turc, Hargreaves-Samani, and Priestley-Taylor techniques, which require less data, can be used as an alternative to PM.…”
Section: Introductionmentioning
confidence: 99%